2004
DOI: 10.1111/j.1751-0813.2004.tb14651.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of one‐step RT‐PCR and a nested PCR for the detection of canine distemper virus in clinical samples

Abstract: The nested PCR detected CDV in blood, urine, nasal swab and saliva more frequently than did the one-step RT-PCR. Therefore, this assay should be a useful aid to antemortem diagnosis of CDV infections in dogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
62
0
5

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(69 citation statements)
references
References 14 publications
0
62
0
5
Order By: Relevance
“…All three viruses are present in South Korea, where 5.1% of dogs are seropositive for CIV and 12.8% are seropositive for CRCoV [2,17]. Using one step RT-PCR, CDV has been detected in 21-70% of clinical samples such as blood, urine, nasal swabs, and saliva [3,23].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…All three viruses are present in South Korea, where 5.1% of dogs are seropositive for CIV and 12.8% are seropositive for CRCoV [2,17]. Using one step RT-PCR, CDV has been detected in 21-70% of clinical samples such as blood, urine, nasal swabs, and saliva [3,23].…”
mentioning
confidence: 99%
“…CRCoV replicates in the upper respiratory tract and can, therefore, be detected in respiratory tissues and nasal swabs [19]. CDV can be detected in various body fluids including urine, blood, saliva, nasal secretions, and cerebrospinal fluid [15,23]. Because all these three viruses can be detected in nasal secretions, hence nasal swabs were used for the mRT-PCR assay.…”
mentioning
confidence: 99%
“…When using conventional reaction, the limit of detection of N gene of CDV was increased hundred fold using the One-Step RT-PCR combined with the NESTED PCR (kIM et al, 2001). The CDV was detected in 50.0% of urine samples from symptomatic dogs by One-Step RT-PCR and in 75.0% of urine samples when combined with NESTED-PCR (SHIN et al, 2004). Thus, in the present study, the System A showed superior analytical sensitivity compared to System B due to greater reaction efficiency.…”
Section: Resultsmentioning
confidence: 58%
“…This gene and its protein are currently subject to many studies due to its importance on transcription, replication and encapsidation of the RNA genome (Stettler and Zurbriggen 1995). In the same way, the sequencing of N gene is essential due to its use for molecular diagnostic, mainly in RT-PCR (Shin et al 1995, Frisk et al 1999, Kim et al 2001, Shin et al 2004 and Real Time RT-PCR (Elia et al 2006, Scagliarini et al 2007.…”
Section: Discussionmentioning
confidence: 99%
“…RNA was eluted in 15 µl of nuclease free water (Fermentas, USA). A pair of primers previously reported by (Shin et al 2004) was used to amplify a 297 bp fragment of the N gene. RT-PCR was performed using the Access Quick RT-PCR Kit (Promega, USA).…”
Section: Methodsmentioning
confidence: 99%